The roles of brand experience in forming loyalty intention - Lada, Suddin; Mohd Suki, Norazah; Md. Sidin, Samsinar (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2014)
Drawing from observations on branding theories, this study aims to examine the roles of brand experience dimensions (i.e. sensory, affective, behavioral, and intellectual) in forming loyalty intention towards sports brands. A survey based quantitative approach is employed to examine the posited hypotheses. A total of 320 participants were involved in the final sample. Analysis of structural equation modeling (SEM) revealed that out of four dimensions of brand experience, sensory had the most significant effect on consumer loyalty intention towards sports brands, followed by affective factor and behavioral factor. Marketing practitioners have come to realize that understanding how consumers experience brands is critical for developing marketing strategies that help to increase positive brand experience. Direction for future research is also provided.